2017
DOI: 10.1051/matecconf/201711507002
|View full text |Cite
|
Sign up to set email alerts
|

Density effect on the mixing efficiency and flow modes in T-shaped micromixers

Abstract: Abstract. Flow patterns and mixing of liquids with different densities in T-shaped micromixers are numerically investigated at Reynolds number range from 1 to 250. The density ratio of the mixing media varies from 1 to 2; its effect on the flow structure and the mixing is studied. The dependences of the mixing efficiency and the pressure difference in this mixer on the density ratio and the Reynolds number are obtained. It is shown that the density ratio has a considerable effect on the flow structure, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It was shown in [14][15][16][17][18][19][20][21][22] that the value of the critical Reynolds number depends on the thermophysical properties of mixing fluids. Thus, it was found that as the fluids viscosities ratio increases the critical Reynolds number increases too, but such value doesn't depend on the fluids densities ratio.…”
Section: Figure 1 the Geometric Configuration Of The Taskmentioning
confidence: 99%
“…It was shown in [14][15][16][17][18][19][20][21][22] that the value of the critical Reynolds number depends on the thermophysical properties of mixing fluids. Thus, it was found that as the fluids viscosities ratio increases the critical Reynolds number increases too, but such value doesn't depend on the fluids densities ratio.…”
Section: Figure 1 the Geometric Configuration Of The Taskmentioning
confidence: 99%
“…The numeric technique used in this paper and the results of its testing are described in detail in the papers [23][24][25]. To solve the system of nonlinear differential Equations (1)-(5), we used the finite-volume method (FVM) [36,37].…”
Section: Mathematical Model and Numerical Computation Methodsmentioning
confidence: 99%
“…During the conducted computations, the PD and the ME were calculated. To quantify the mixing efficiency, the parameter M = 1 − (σ/σ 0 ) 0.5 was used [20][21][22][23][24][25]41,42], where…”
Section: Mathematical Model and Numerical Computation Methodsmentioning
confidence: 99%
“…That regime is of the greatest interest for researchers because the mixing efficiency increases abruptly in this mode while the pressure drop in the mixing channel increases insignificantly. On the other side, the investigations of mixing of two fluids with different thermophysical properties were carried out by many researchers [14][15][16][17][18][19][20]. For example, a systematic study of the viscosity effect on mixing modes in the T-shaped micromixer was carried out in [14], where the significant effect of viscosities ratio on the flow structure before and after the transition from symmetric to asymmetric flow regimes was shown.…”
Section: Introductionmentioning
confidence: 99%
“…The self-similar behaviour of the asymmetric flow regime was observed. A systematic study of the density effect on mixing modes in the T-shaped micromixer was carried out in [15], and it was shown that the change in the density of one of the miscible fluids does not lead to a shift of flow regimes. However, a significant flow asymmetry in the region before its transition to the engulfment flow mode was observed.…”
Section: Introductionmentioning
confidence: 99%